Nano-pesticidal potential of Cassia fistula (L.) leaf synthesized silver nanoparticles (Ag@CfL-NPs): Deciphering the phytopathogenic inhibition and growth augmentation in Solanum lycopersicum (L.) - Danish, Mohammad; Shahid, Mohammad; Ahamad, Lukman; Raees, Kashif; Atef Hatamleh, Ashraf; Al-Dosary, Munirah Abdullah; Mohamed, Abdullah; Al-Wasel, Yasmeen Abdulrhman; Singh, Udai B.; Danish, Subhan (Frontiers in Microbiology, 2022)
Plant-based synthesis of silver nanoparticles (Ag-NPs) has emerged as a potential alternative to traditional chemical synthesis methods. In this context, the aim of the present study was to synthesize Ag-NPs from Cassia fistula (L.) leaf extract and to evaluate their nano-pesticidal potential against major phyto-pathogens of tomato. From the data, it was found that particle size of spherical C. fistula leaf synthesized (Ag@CfL-NPs) varied from 10-20 nm, with the average diameter of 16 nm. Ag@CfL-NPs were validated and characterized by UV-visible spectroscopy (surface resonance peak λmax=430 nm), energy dispersive spectrophotometer, Fourier transform infrared (FTIR), and X-ray diffraction pattern, and electron microscopy; scanning electron microscopy (SEM) and transmission electron microscopy. The FTIR spectra verified the participation of various living molecules (aromatic/aliphatic moieties and proteins) in synthesized Ag@CfL-NPs. The anti-phytopathogenic potential of Ag@CfL-NPs was assessed under in-vitro conditions. Increasing doses of Ag@CfL-NPs exhibited an inhibitory effect against bacterial pathogen Pseudomonas syringae and 400 µg Ag@CfL-NPs mL-1 caused a reduction in cellular viability, altered bacterial morphology, and caused cellular death Furthermore, Ag@CfL-NPs reduced exopolysaccharides (EPS) production and biofilm formation by P. syringae Additionally, Ag@CfL-NPs showed pronounced antifungal activity against major fungal pathogens. At 400 µg Ag@CfL-NPs mL-1, sensitivity of tested fungi followed the order: Fusarium oxysporum (76%)>R. solani (65%)>Sarocladium (39%). Furthermore, 400 µg Ag@CfL-NPs mL-1 inhibited the egg-hatching and increased larval mortality of Meloidogyne incognita by 82 and 65%, respectively, over control. Moreover, pot studies were performed to assess the efficacy of Ag@CfL-NPs to phyto-pathogens using tomato (Solanum lycopersicum L.) as a model crop. The applied phyto-pathogens suppressed the biological, physiological, and oxidative-stress responsiveness of tomatoes. However, 100 mg Ag@CfL-NPs kg-1 improved overall performance and dramatically increased the root length, dry biomass, total chlorophyll, carotenoid, peroxidase (POD), and phenylalanine ammonia lyase (PAL) activity over pathogens-challenged tomatoes. This study is anticipated to serve as an essential indication for synthesis of efficient nano-control agents, which would aid in the management of fatal phyto-pathogens causing significant losses to agricultural productivity. Overall, our findings imply that Ag@CfL-NPs as nano-pesticides might be used in green agriculture to manage the diseases and promote plant health in a sustainable way.